A Case of Haemophilus haemolyticus Meningitis - Jane Qu; Sunil R. Ramaswamy; Rodolfo M. Alpizar-Rivas (Annals of Internal Medicine: Clinical Cases)
Haemophilus haemolyticus is a gram-negative bacillus respiratory tract commensal with reduced capacity to invade mucosal epithelia. Nontypeable (that is, nonencapsulated) Haemophilus influenzae and H haemolyticus are difficult to differentiate from each other but, due to advancements in genotype assays, H haemolyticus has been found to cause invasive disease. We describe a rare case of H haemolyticus bacteremia and meningitis in a 50-year-old man who presented with altered sensorium. He was found to have a low IgM level, leading to speculation that a decreased immune system contributed to his presentation. However, he ultimately declined further immunosuppressive work-up.